كەسایەتی د رۆمانا (شەڤێن پراگ) یا (حەسەن ئیبراهیم)ی ل دویڤ تیورا دەروونشیكاریا (ئێریك فرۆم)ی - ISMAIL , HARJEEN YASSEN; KHALID, IMAD WAISI (Journal of Duhok University, 2023)
Character is considered one of the basic literary genres and the pillar for writing a novel. Because of the significance of this genre, several studies on various aspects have been conducted. The psychological aspect is one of these. Psychiatrists investigate the qualities of each person in society based on their behavior and categorize them based on the beliefs of Sigmond Freud, Alfred Adler, and Erich Fromm. Erich Fromm sheds light on the relationship between characters and society, classifying their tasks and responsibilities according to productivity and nonproductivity. This research attempts to analyze the term "character" in literary genres using Erich Fromm’s psychological theory and applying it to Hassan Ibrahim’s "Prague Nights."